Physical education and sport a contemporary introduction - Lumpkin, Angela (McGraw-Hill, 1998)
This edition exposes students to the history, philosophies and principles of today's physical education programmes within a careers-oriented framework. It contains an increased emphasis on the non-traditional careers that are becoming more common as the field expands.